Atividade antileishmania do fulerol e efeito hepatoprotetor na quimioterapia antimonial em modelo murino de leishmaniose visceral - Guilherme Santos Ramos (2014)
Due to the limitations of the actual treatment of leishmaniasis using pentavalent antimonials, such as glucantime, a first aim of this study was to evaluate the impact of fullerol, which is a spherical water-soluble carbon nano particle and a potent antioxidant, in the prevention of hepatotoxicity caused by glucantime. For the first time, the fullerol antileishmanial activity was assessed in vitro and in vivo using a murine model of visceral leishmaniasis (VL). Both evaluations of efficacy and toxicity were performed in BALB/c mice infected with L. infantum,which received free fullerol (0,05 mg/kg) for 20 days intraperitoneally or liposome-encapsulated fullerol (0.05 or 0.2 mg/kg/4 days), with or without glucantime (120 mg Sb/ kg/day). Positive and negative controls received glucantime and saline, respectively. Evaluation of parasite load by quantitative PCR showed, surprisingly, that treatment with daily doses of free fulerol 0.05 mg/kg significantly reduced the liver and spleen parasite burdens at levels equivalent to those of the group treated with glucantime. When doses were given every 4 days, only liposomal fullerol caused a significant reduction in parasite load. In the group that received liposomal fullerol at 0.2 mg/kg, the number of parasites was significantly lower than in glucantime group, and we could not detect parasite in the liver. While treatment with glucantime associated with fullerol showed a similar efficacy compared to free fullerol, there was a significant reduction of liver histopatological changes when compared to the group treated with only glucantime. The benefits include reduction in the proportion of swollen hepatocytes and apoptotic index, supported by TUNEL assay. Regarding in vitro leishmanicidal activity, the use of fullerol at a non-cytotoxic concentration to peritoneal macrophages (0.12 mg/ml) significantly reduced by 75% the number of amastigotes inside macrophages. In conclusion, our data establish for the first time the antlieishmanial activity of fullerol and its protection against glucantime hepatotoxicity in murine modelof VL, showing potential as drug against VL.